Response of normal human cells to stress causing agents and their relationship with ageing and cellular resistance - Burgos-Molina, Antonio Manuel; Peinado-Ruiz, Isabel C.; González Vidal, Alejandro; Ruiz-Gómez, Miguel José (2022)
By applying low doses of a stressor, normal cells increase the number of HSP leading to increased survival. This phenomenon is considered a cellular adaptive response. The results show that treatment with low doses of a stressor improve the functional capacity of human cells in terms of greater resistance to stress, increased proteasome activity, and reduced lipofuscin accumulation. There is evidence of oxidative modiﬁcation of a speciﬁc transcription factor in aged cells. In this sense, ageing affects the function, distribution and modiﬁcation that HSP proteins undergo. Previous induction by heat at low doses is beneﬁcial for the expression of HSP70 and the subsequent increase in cellular resistance to hypoxic and oxidative stress factors. The fact that normal human cells are subjected to low doses of a stressor could be beneﬁcial in vitro, since it increases the concentration of HSP70, HSC70, HSP27 and decreases the level of HSP90. These alterations increase cell resistance in vitro to oxidative, hypoxic and thermal factors, as well as increase proteasome activity, improve cell morphology and vigor, and favor a longer cell life cycle.
Keywords: Células humanas - Investigación; Stress-causing agents; Ageing and celular resistance